Top Clean Launderette / Khairil Iswan Mohd Yusoff ... [et al.] - Mohd Yusoff, Khairil Iswan; Sulong, Ahmad Rusdi; Daud, Anas; Nik Sen, Nik Mohd Fikeri; Md Nuron, Mohd Hailmi (Faculty of Civil Engineering, 2006)
Our company name is TOP CLEAN LAUNDERETTE. From the name, it already shows what are the activities of our company doing. We believe the word Laundrette make customer understand that we are doing laundry activities such as washing, drying, ironing clothes, dry cleaning, curtain, mattress and other fabric. The word TOP' also show that we will be the top laundry at Shah Alam. We hope our company will be listed as among the top laundry. Besides it also unique name and easy to remember and speak.